2020
DOI: 10.2174/1570159x18666200221113842
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Chemotherapy-induced Cognitive Impairment and Potential Role of Antidepressants

Abstract: Background: Cognitive impairment is an adverse reaction of cancer chemotherapy and is likely to affect up to 75% of patients during the treatment and 35% of patients experience it for several months after the chemotherapy. Patients manifest symptoms like alteration in working ability, awareness, concentration, visual-verbal memory, attention, executive functions, processing speed, fatigue and behavioural dysfunctions. Post-chemotherapy, cancer survivors have a reduced quality of life due to the symptoms of che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 95 publications
(92 reference statements)
0
18
0
Order By: Relevance
“…Chronic treatment with chemotherapeutic agents causes a deficit in central BDNF levels, affecting neuronal functions (NG et al 2015). Approaches to resume the BDNF levels in the brain by certain drugs such as antidepressants (Fluoxetine) have been discussed and provide their scope of implication as a therapeutic strategy for CICI (Das et al 2020).…”
Section: Impaired Neurogenesismentioning
confidence: 99%
“…Chronic treatment with chemotherapeutic agents causes a deficit in central BDNF levels, affecting neuronal functions (NG et al 2015). Approaches to resume the BDNF levels in the brain by certain drugs such as antidepressants (Fluoxetine) have been discussed and provide their scope of implication as a therapeutic strategy for CICI (Das et al 2020).…”
Section: Impaired Neurogenesismentioning
confidence: 99%
“…And, a recent double-blind randomized controlled trial showed that compared with minimum acupuncture stimulation, electroacupuncture trigeminal nerve stimulation plus body acupuncture showed advantages in improving the quality of life of cancer patients and reducing working memory impairment [119]. At the same time, antidepressants such as fluoxetine may alleviate CRCI by balancing cytokines [120]. Aspirin is known to have anti-inflammatory properties.…”
Section: Othersmentioning
confidence: 99%
“…It is known that docetaxel compromises the structural integrity of the cerebral cortex and peripheral neurons [ 51 ]. Both doxorubicin and cyclophosphamide induced behavioral impairments, although only the last was associated with inflammation caused by microglia [ 52 ]. Variable levels of cytokine concentrations and cognitive impairment severity are associated with distinct chemotherapy regimens and doses.…”
Section: Discussionmentioning
confidence: 99%